High-level indicators developed by PIM assist USAID in targeting food security investments and tracking progress of the Global Food Security Strategy in focal countries - CGIAR Research Program on Policies, Institutions, and Markets (2019)
With PIM support, IFPRI developed measures of agri-food system gross domestic product (AgGDP+) and employment (AgEMP+) which USAID is using as high-level outcome indicators for its Global Food Security Strategy (GFSS). The choice of these indicators will influence the nature of USAID country mission investments and other programming within GFSS focal countries.